FACTORS INFLUENCING PROVISION OF HEALTH CARE IN A DEVOLVED SYSTEM OF GOVERNMENT, BUNGOMA COUNTY, KENYA - Kipruto, Arap Kirwa; Letting, Nicholas (Global Journal of Health Sciences, 2017)
Purpose: The general objective of the study was to assess the factors influencing provision of health care in a devolved system of government, with a special focus on Bungoma County. Methodology: The research design was a descriptive survey utilizing both the quantitative and qualitative aspect. The target population will be all the heads of the health facilities in Bungoma County. The sampling technique will be Non Probability Sampling where Purposive Sampling will be used to identify all the heads of government hospitals, Health Centers and dispensaries in the county as they possess the relevant knowledge required for the study. Questionnaires will then be used to obtain primary data. The Statistical Package for Social Sciences (SPSS version 12) was used to analyze quantitative data and presented using descriptive statistics. Qualitative data will be analyzed using thematic analysis and presented in form of narratives and themes. Results: Based on the findings the study concluded that disbursement and adequacy of finances, supplies and equipment affected health care provision in a devolved system of government. The study also concluded that drugs procurement challenges affected health care provision in a devolved system of government. Findings further concluded that disbursement and adequacy of finances, supplies and equipment has a positive and significant effect on health care provision as supported by (r=0.502, p=0.002).However, procurement challenges has a positively and insignificant association on health care provision as supported (r=0.309, p=0.603) The results revealed that healthcare personnel had a positively and a significantly association to health care provision (r=0.406, p=0.013). Policy recommendation: The findings of this study will be of great significance to the ministries of Health and that of Devolution and Planning plus the County Governments in Kenya on the factors that face devolution of health in order to come up with practical solutions.